DAMPAK MASYARAKAT EKONOMI ASEAN TERHADAP PENGGUNAAN TENAGA KERJA ASING DI PROVINSI RIAU TAHUN 2015-2017 - Ana Septiana; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research explain about the effect of ASEAN Economic Community (AEC) toward the foreign worker at Riau province. After the prevailing of MEA, there are an increase of foreign worker who came to Indonesia especially to Riau province, this phenomenon occured due to of MEA has erase some obstacles in certain current such as product, service, investment, skill workers and of course those things will bring an effect itself after the prevailing of MEA toward the using of foreign worker at Riau province. The perspective used in this research is Liberalism Perspective with International Cooperation Theory. The data used in this research is secondary data that obtained through kinds of literature such as books, journals, newspapers, certain institution data and other document that support this research. The data obtained was selected and then being analyzed in a qualitative way and arranged in form of descriptive research report. The result of this research, after the prevailing of MEA toward the using of foreign worker at Riau province, it has either positive and negative effects. The negative effect such, MEA create such a competition between foreign and local worker, MEA could make a foreign worker who came to Indonesia to replace the position of local worker in a work field, therefore the positive effect of MEA is we would have a lot of foreign investment coming and there will be a transfer in terms of technology and knowledge in the future.Keyword: ASEAN Economic Community (AEC), foreign worker, ASEAN, Riau Province